Gender, Islam, and democracy in Indonesia [ - Robinson, Kathryn May , 1949- (Asian Studies Association of Australia women in Asia series, 2009)
"Exploring the relationship between gender, religion and political action in Indonesia, this book examines the patterns of gender orders that have prevailed in recent history, and demonstrates the different forms of social power this has afforded to women. Written in an accessible way, Gender, Islam and Democracy in Indonesia explores the part played by women in the nationalist movement, as well as the role of the women's movement in the structuring of the independent Indonesian state, the politics of the immediate post-independence period and the transition to the authoritarian New Order. The book analyzes: the gender relations of the New Order regime the implications of the opening up of the economy to foreign capital and ideas for conceptions of gender relations the forms of political activism that were possible for the women's movement under the New Order, and the role it played in the fall of Suharto and the transition to democracy the relationship between Islam and women in Indonesia. This is an impressive account of the relationship between gender, religion and democracy in Indonesia, and is a vital resource for students of gender studies and Indonesian affairs."--Book cover.